2019
DOI: 10.3389/fnana.2018.00116
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of NPY and Somatostatin-28 Peptidergic Populations in the Human Angular Bundle

Abstract: The angular bundle is a white matter fiber fascicle, which runs longitudinally along the parahippocampal gyrus. It is best known for carrying fibers from the entorhinal cortex (EC) to the hippocampus through the perforant and alvear pathways, as well as for carrying hippocampal output to the neocortex, and distributing fibers to polysensory cortex. The angular bundle is already present prenatally at the beginning of the fetal period. Connections between the EC and the hippocampus are established by the 20th ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…For the potentially inhibitory subpopulations of WMICs in the chimpanzee, in relation to the estimates of the total number of WMICs, the largest subpopulation was the CR+ neurons (~12.1%), followed by the nNOS+ neurons (~10.5%), and a very small subpopulation of PV immunopositive cells. Combining the CR and nNOS results, we can provisionally report that the percentage of immunohistochemically identified inhibitory WMICs is ~22.6% of the total estimate of WMICs; however, this proportion is tentative, as the possible presence, or neurochemical overlap, with the markers used and other potential markers such as neuropeptide Y or somatostatin (e.g., Cebada‐Sánchez et al, 2019), were not explored in the current study. Our analysis of the proportion of inhibitory WMICs is well within the estimates provided for cortical inhibitory neurons in human and nonhuman primates, which ranges from 20% to 29% (Džaja et al, 2014; Hornung & de Tribolet, 1994; Krienen et al, 2020; Rudy et al, 2011; Sherwood et al, 2007, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…For the potentially inhibitory subpopulations of WMICs in the chimpanzee, in relation to the estimates of the total number of WMICs, the largest subpopulation was the CR+ neurons (~12.1%), followed by the nNOS+ neurons (~10.5%), and a very small subpopulation of PV immunopositive cells. Combining the CR and nNOS results, we can provisionally report that the percentage of immunohistochemically identified inhibitory WMICs is ~22.6% of the total estimate of WMICs; however, this proportion is tentative, as the possible presence, or neurochemical overlap, with the markers used and other potential markers such as neuropeptide Y or somatostatin (e.g., Cebada‐Sánchez et al, 2019), were not explored in the current study. Our analysis of the proportion of inhibitory WMICs is well within the estimates provided for cortical inhibitory neurons in human and nonhuman primates, which ranges from 20% to 29% (Džaja et al, 2014; Hornung & de Tribolet, 1994; Krienen et al, 2020; Rudy et al, 2011; Sherwood et al, 2007, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…In the rostral and middle levels (Figure b′,c′,d′), the amc, the anterior part of the angular bundle (ab) that forms the ventral border of the amygdaloid complex (Morais et al, ), was observed. At the caudal levels, the perforant pathway (pep) fibers entered the underlying ab, which corresponds to the tract placed in the ventromedial part of the medial temporal lobe (Cebada‐Sánchez, Marcos Rabal, Insausti, & Insausti, ). The entorhinal fibers then traversed the subiculum and crossed the hippocampal fissure to enter the dentate gyrus, or the subiculum and the hippocampus (Figure e′,f′).…”
Section: Resultsmentioning
confidence: 99%
“…Of these potential five types identified with the restricted approach used herein, four are specifically identified as GABAergic inhibitory due to these cells being immunopositive for parvalbumin, calbindin, calretinin (although calretinin can be excitatory, Gabbott, 2016) excitatory neuron within the WMIC population in the megachiropterans. It is likely that additional neurochemical types of both excitatory and inhibitory neurons will be present, in particular inhibitory neurons producing somatostatin, neuropeptide Y or neurotensin (Barbaresi et al, 2014;Cebada-Sánchez, Rabal, Insausti, & Insausti, 2019;Tomioka & Rockland, 2007), and with the potential for different combinations of marker coexpression. Given that in the current study the calbindin and nNOS immunopositive WMICs account for~26% of the total WMIC population, the numbers/proportions of these additional inhibitory neuronal types are likely to be minimal, as this proportion of inhibitory WMIC neurons is in line with the proportions of inhibitory WMICs reported in rodents (15-25%, Clancy et al, 2009), the lar gibbon (23.1%, Swiegers et al, 2019), and humans (25%, García-Marin et al, 2010).…”
Section: Types and Proportions Of Wmicsmentioning
confidence: 99%